Aurignacian osseous points from the Potočka zijalka cave (Slovenia): Interpreting the new results of a morphometric statistical analysis - Turk, Matija; Turk, Ivan (Arheološki vestnik, 2020)
After ninety years since its discovery, the 134 massive-based Aurignacian osseous points from the cave site of Potočka zijalka still represent the largest collection of its kind in Europe and the subject of numerous and varied studies. They were found in two layers in two different areas of the cave with different habitation and sedimentation microenviron- ments. Most are either flat or spindle-shaped with regards to their longitudinal cross section or side contour, each with its own set of technical properties and present at both areas of the cave. There are also single examples of several monotypes, including a Mladeč type point. Of the two main types, 117 points are systematically analysed here for the first time using standard parametric and non-parametric statistical procedures based on a combination of twenty vari- ables, nine of them metric and eleven descriptive. The results of the analysis have led to new observations concerning the presumed technical improvements of Aurignacian points, the way the points were hafted, repairs of damaged points, manufacture of blanks for large points and the significance of the cuts and incisions occurring on some of them. They have also shown the spindle-shaped points from Potočka zijalka as a technically accomplished shape of massive-based point meriting the name the Potočka zijalka or Olševa point.